2021
DOI: 10.1038/s41420-020-00383-y
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell long noncoding RNA (lncRNA) transcriptome implicates MALAT1 in triple-negative breast cancer (TNBC) resistance to neoadjuvant chemotherapy

Abstract: Cumulative evidence suggests added benefit for neoadjuvant chemotherapy (NAC) in a subset of triple-negative breast cancer (TNBC) patients. Herein we identified the long noncoding RNA (lncRNA) transcriptional landscape associated with TNBC resistance to NAC, employing 1758 single cells from three extinction and three persistence TNBC patients. Using Iterative Clustering and Guide-gene Selection (ICGS) and uniform manifold approximation and projection (UMAP) dimensionality reduction analysis, we observed single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 45 publications
(54 reference statements)
6
39
0
Order By: Relevance
“…MALAT1 was the most downregulated lncRNA in response to DNMTi of TNBC. Our recent data implicated MALAT1 in TNBC resistance to neoadjuvant chemotherapy where we showed CRISPR-Cas9 mediated MALAT1 promoter deletion to reduce CFU and enhance sensitivity of TNBC cells to chemotherapy, hence corroborating data from current study [ 73 ].…”
Section: Discussionsupporting
confidence: 90%
“…MALAT1 was the most downregulated lncRNA in response to DNMTi of TNBC. Our recent data implicated MALAT1 in TNBC resistance to neoadjuvant chemotherapy where we showed CRISPR-Cas9 mediated MALAT1 promoter deletion to reduce CFU and enhance sensitivity of TNBC cells to chemotherapy, hence corroborating data from current study [ 73 ].…”
Section: Discussionsupporting
confidence: 90%
“…MALAT1 was expressed more highly than any other lncRNA in both T1 and T2, which is in agreement with the literature [10]. MALAT1 has been shown to be a prognostic marker in TNBC [49], and implicated in therapeutic resistance [50] and metastasis in breast cancer [51]. It appears to affect the malignant phenotype by chromatin binding, and as a splicing modulator [52].…”
Section: Discussionsupporting
confidence: 85%
“…Recent studies revealed that lncRNAs acted as a key regulator in the pathogenesis, progression, and phenotype development of breast cancer (32). Growing data delineated LncRNAs dysregulated in breast cancer (33)(34)(35)(36)(37). As previously described, lncRNA FGD5-AS1 participated as an essential mediator in various cancer.…”
Section: Discussionmentioning
confidence: 71%